Sponge‐Like Microfiber Electrodes for High‐Performance Redox Flow Batteries. Issue 10 (25th August 2022) - Sun, Jing; Wan, Yuhan; Jian, Qinping; Fan, Xinzhuang; Zhao, Tianshou
Abstract: Fabricating fiber‐based electrodes with a large specific surface area while maintaining high flow permeability is a challenging issue in developing high‐performance redox flow batteries. Here, a sponge‐like microfiber carbon electrode is reported with a specific surface area of as large as 853.6 m 2 g −1 while maintaining a fiber diameter in the range of 5–7 µm and a macropore size of ≈26.8 µm. The electrode is developed by electrospinning cross‐linked poly(vinyl alcohol)‐lignin‐polytetrafluoroethylene precursors, followed by oxidation and pyrolysis. Applying the as‐synthesized electrodes to a vanadium redox flow battery enables the battery to achieve an energy efficiency of 79.1% at the current density of 400 mA cm −2 and a capacity retention rate of 99.94% over 2000 cycles, representing one of the best battery performances in the open literature. The strategy to fabricate sponge‐like porous carbon microfibers holds great promise for versatile applications in redox flow batteries and other energy storage systems. Abstract : Sponge‐like microfiber electrodes are fabricated through electrospinning cross‐linked poly(vinyl alcohol), lignin, and polytetrafluoroethylene precursor solutions and post‐treatments. The as‐prepared electrodes enable a vanadium redox flow battery to achieve a 79.1% energy efficiency at 400 mA cm −2, and a limiting current of 4000 mA cm −2 .